Creative knowledge transfer using junk art to promotes sustainable development goals / Nur Fatin Yahawa and Siti Zuraida Maaruf. - Yahawa, Nur Fatin; Maaruf, Siti Zuraida (Universiti Teknologi MARA Cawangan Selangor, 2019)
The process of getting information regarding government initiatives to promote entrepreneurship (2016-2020) in rural area has not been clearly explained to the population in rural areas. The development of an alternative teaching and learning module has enabled for meaningful. There is a need to develop an alternative teaching and learning module to support the transfer of knowledge and skills. The aim of this study was to design and develop Junk Art Module as scaffolding for unemployed women to obtain knowledge and skills in art production. The study was conducted using the Design and Developmental Research (DDR) by Richie and Klein (2007). There were eight unemployed women and three experts from government agencies who were involved in this research. To test the usability of the module, the researchers conducted interview sessions with the experts and unemployed women which showed that the Junk Art Module offered a new knowledge and skills in producing art products using recycled items which should be commercialized through online businesses, tourism centers and other market places. Both the experts and unemployed women gave positive feedback that the module gave them a positive experience in in making art products as a sustainable goal.